Lenticular‐Lens‐Based Colored Antiglare Dashboard Surfaces. Issue 1 (7th November 2016) - Ji, Chengang; Zhu, Guodong; Zhang, Cheng; Nam, Sunghyun; Li, Qiaochu; Xia, Liangping; Zhang, Weiguo; Banerjee, Debasish; Guo, Lingjie Jay
Abstract : All current vehicle dashboards are black in order to prevent any veiling glare that interferes safe driving. Here, the authors report on a novel design of surface that can impart color to the dashboard and does not cause veiling glare to the driver. This is made possible by covering a substrate with alternating absorber/colored stripes with specially designed lenticular lens arrays, where reflected light rays are controlled out of the veiling glare range while at the same time create visual colors to drivers. As an experimental demonstration, a 3.5 cm 2 square sample is fabricated by imprinting method. The presented approach provides a new application of lenticular lenses and can be potentially applied to embellish vehicles' interiors. Due to the small pitches (≈50 µm) of lenses, the proposed method can even be extended for vehicle displays with high resolutions if integrating with active devices. Abstract : A novel colored dashboard without veiling glare is designed and experimentally demonstrated based on the combination of a lenticular lens array and an alternating absorber/colored stripe substrate. By employing the thermal imprinting method, this reported scenario with significantly reduced manufacturing cost can be potentially applied for mass production and open up a new path for the application of lenticular lenses.